THE AESTHETICS OF MISERY: AN INTERPRETATION AND COMPARATION IN CONTEMPORARY INTERIOR DESIGN - Jamaludin Jamaludin; Anwar Subkiman (Fakultas Seni Rupa dan Desain ITB, 2018)
This paper discusses symbolic interior design and contemporary which are relevant to the experimental work called Aesthetics of Misery presented at the Milan Furniture Fair in April 2015. The exhibition presented sixteen works by students of the Interior Design Postgraduate Program at Politechnico di Milano Italia. This new approach to design was launched by Andrea Branzi and Michele de Lucchi, the two main designers at Milan. Viewed from aesthetics, the works on display have symbolic aesthetic elements. The works display a